13x-6=6x+15

Simple and best practice solution for 13x-6=6x+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13x-6=6x+15 equation:


Simplifying
13x + -6 = 6x + 15

Reorder the terms:
-6 + 13x = 6x + 15

Reorder the terms:
-6 + 13x = 15 + 6x

Solving
-6 + 13x = 15 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-6 + 13x + -6x = 15 + 6x + -6x

Combine like terms: 13x + -6x = 7x
-6 + 7x = 15 + 6x + -6x

Combine like terms: 6x + -6x = 0
-6 + 7x = 15 + 0
-6 + 7x = 15

Add '6' to each side of the equation.
-6 + 6 + 7x = 15 + 6

Combine like terms: -6 + 6 = 0
0 + 7x = 15 + 6
7x = 15 + 6

Combine like terms: 15 + 6 = 21
7x = 21

Divide each side by '7'.
x = 3

Simplifying
x = 3

See similar equations:

| 2(x-2)+46=-4x | | 3x+8=4x-22 | | 3(x-4)-14=2(x-7)+7 | | 3x+5y+11=4(5x-2y) | | 2x^2-3x=40 | | 13x=6x+42 | | x^6+x^2= | | 4x^2+5=20 | | x+(x+6)+2x=94 | | 6n+3=63 | | 5(3y-1)-1(2y)=10 | | x^2-37=0 | | -5x^2+10x=0 | | -3+n=-91 | | -2x=7y-19 | | -17=63+n | | 2+5*3+4= | | 35x^2+x-6=0 | | n+(-3)=-91 | | 7.32xA=13.53+2.81xA | | 9+2(x-7)=0 | | 2x+(3x+4)=4 | | 92=6+3w | | 92=6+1/2 | | 7x-4=2x+2 | | 92=2+6w | | 0x-.99-3x=-15 | | 92=6+2w | | 2a^2=196 | | 0.4x=8 | | 315=21s | | 15x^2=-3-14x |

Equations solver categories